2020
DOI: 10.1101/gad.342873.120
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-autonomous feedback down-regulates meiotic DNA break competence upon synaptonemal complex formation

Abstract: The number of DNA double-strand breaks (DSBs) initiating meiotic recombination is elevated in Saccharomyces cerevisiae mutants that are globally defective in forming crossovers and synaptonemal complex (SC), a protein scaffold juxtaposing homologous chromosomes. These mutants thus appear to lack a negative feedback loop that inhibits DSB formation when homologs engage one another. This feedback is predicted to be chromosome autonomous, but this has not been tested. Moreover, what chromosomal process is recogni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 66 publications
(133 reference statements)
3
60
0
Order By: Relevance
“…Prior studies indicate that budding yeast SC assembly prevents excess Spo11-initiated DSBs (Subramanian et al . 2016; Mu et al . 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies indicate that budding yeast SC assembly prevents excess Spo11-initiated DSBs (Subramanian et al . 2016; Mu et al . 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The budding yeast SC structure thus plays a role in attenuating interhomolog recombination events, possibly by discouraging the accumulation of additional DNA DSBs, and/or by preventing nascent recombination intermediates from engaging with the homolog (versus the sister chromatid) for repair (Subramanian et al . 2016; Mu et al . 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This revealed that excessive DSB formation is controlled by a regulatory feedback mechanism that depends on interhomolog interactions ( Figure 9A , circuit 7). Yeast strains with karyotype abnormalities show accumulation of DSBs specifically on the chromosomes that experience homolog engagement defects, showing that the feedback control operates in a chromosome-autonomous fashion ( Mu et al, 2020 ). Smaller chromosomes also experience higher DSB levels, in part because they take more time to find each other, and as a consequence remain longer in a DSB-competent state due to the persistence of DSB proteins ( Murakami et al, 2020 ).…”
Section: Regulation Of Dsb Formationmentioning
confidence: 99%
“…Mutations in components of the SC central region (Gmc2 and Ecm11) that abolish SC elongation but not crossover formation show elevated DSBs ( Humphryes and Hochwagen, 2014 ; Voelkel-Meiman et al, 2016 ; Lee et al, 2020 ; Mu et al, 2020 ). This indicates that homolog engagement feedback control operates at the level of SC assembly rather than recombination.…”
Section: Regulation Of Dsb Formationmentioning
confidence: 99%
See 1 more Smart Citation